1970
DOI: 10.3329/icpj.v1i1.9218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesic, neuropharmacological and cytotoxic activity of <i>Trigonella foenum-graecum</i> Linn.

Abstract: The present study was carried out to investigate the possible analgesic, neuropharmacological and cytotoxic activities of the methanolic extract of Trigonella foenum-graecum Linn. leaves. The analgesic and neuropharmacological activities of Trigonella foenum-graecum Linn. were investigated at the doses of 100mg/kg, 200mg/kg and 400mg/kg of body weight in mice. Analgesic potential of the extract was evaluated for centrally acting analgesic property using tail immersion method and peripheral analgesic actions us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Multiple studies have reported that phytochemical compounds possess sedative and hypnotic effects, including tannins which can cause nonspecific CNS depression [56][57][58]. Several such action mechanisms have been proposed for alkaloids, flavonoids, steroids, as well as terpenoids, including activation of protein kinase C, neuroprotection against oxidative and metabolic insults; enhancing nicotinic receptors that also elevate the sensation and memory; energizing and improving nervous function; activating the transient receptor calcium channels in the membrane of the nerve cell which have neuropharmacological influence [59][60][61][62][63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported that phytochemical compounds possess sedative and hypnotic effects, including tannins which can cause nonspecific CNS depression [56][57][58]. Several such action mechanisms have been proposed for alkaloids, flavonoids, steroids, as well as terpenoids, including activation of protein kinase C, neuroprotection against oxidative and metabolic insults; enhancing nicotinic receptors that also elevate the sensation and memory; energizing and improving nervous function; activating the transient receptor calcium channels in the membrane of the nerve cell which have neuropharmacological influence [59][60][61][62][63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%